Physical and optical fractionator techniques - Altun, Gamze; Deniz, Ömür Gülsüm; Kaplan, Arife Ahsen; Kipanyula, Maulilio J.; Kaplan, Süleyman (Nova Science Publishers, Inc., 2024)
Stereological approaches are based on statistics and geometry. These methods can provide information about the volume, length, surface area, and numbers of structures from measurements made from two-dimensional sections or images. Stereological techniques are applied to tissues or organs according to the principles of systematic random sampling and, therefore, provide unbiased and realistic results. The fractionator technique is frequently used to estimate the cell population of an entire organ. It estimates the number of particles irrespective of their shape, orientation, size, and distribution. There are two types of fractionators, optical and physical. The physical fractionator method uses two physically separated sections, i.e., a disector pair, while the optical fractionator method employs one thick section for particle counting. Both apply the same basic logic for tissue evaluation. The optical fractionator technique is frequently employed, especially in neurostereological studies, because of its great efficiency. The probe and sampling steps employed in estimating the cell population in a tissue or organs are of critical importance. Conducting a pilot study before starting the evaluation may be help identify the correct technique and appropriate sampling strategies. Coefficient of error and coefficient of variation values are the parameters that determine the sampling frequency and number of subjects to be analyzed. Reliable results can be obtained using the fractionator method, one of the best stereological techniques, if it possesses optimal coefficient of error and coefficient of variation values.
Keywords: Design-Based Stereology; Disector; Optical Fractionator; Physical Fractionator; Systematic Random Sampling